To solve the quadratic equation \( x^2 - 22x + 1 = 15 \) by completing the square, let's follow these steps:
-
Move the constant to the other side of the equation: \[ x^2 - 22x + 1 - 15 = 0 \implies x^2 - 22x - 14 = 0 \]
-
Rearrange and isolate the \( x^2 \) and \( x \) terms: \[ x^2 - 22x = 14 \]
-
Complete the square:
- Take half of the coefficient of \( x \) (which is -22), square it, and add to both sides. Half of -22 is -11 and \((-11)^2 = 121\). \[ x^2 - 22x + 121 = 14 + 121 \] \[ x^2 - 22x + 121 = 135 \]
-
Rewrite the left side as a squared term: \[ (x - 11)^2 = 135 \]
-
Take the square root of both sides: \[ x - 11 = \pm \sqrt{135} \]
-
Solve for \( x \): \[ x = 11 \pm \sqrt{135} \]
So the solutions are: \[ x = 11 + \sqrt{135} \quad \text{and} \quad x = 11 - \sqrt{135} \]
Now, simplifying \(\sqrt{135}\): \[ \sqrt{135} = \sqrt{9 \times 15} = 3\sqrt{15} \]
Thus, we substitute back: \[ x = 11 + 3\sqrt{15} \quad \text{and} \quad x = 11 - 3\sqrt{15} \]
Therefore, the correct answer is: \[ x = 11 + 3\sqrt{15}, 11 - 3\sqrt{15} \]
Hence, the correct response from the options would be:
- x = 11 + 3\sqrt{15}, 11 - 3\sqrt{15}.